What Do Life-Support Trainers Mean When They Say They Use the Learning Conversation Debriefing Method? A Phenomenographic Study - Jaime C. Smal; Nigel M. Turner; Rob M. Moonen; Marije Hogeveen; Olle Ten Cate (Simulation in Healthcare: The Journal of the Society for Simulation in Healthcare, 2026)
Introduction: Simulation-based medical education (SBME) can help health care professionals to perform effectively in high-stakes situations. Debriefing is a cornerstone of SBME, typically facilitated by trainers using structured frameworks. The post-simulation learning conversation (PSLC) has been described as a 7-step flexible debriefing model. Despite faculty training, PSLC is not always applied consistently. This study aimed to explore variation in how life-support trainers perceive and apply PSLC in simulation debriefing, to identify deviations from the original format, and to improve understanding of this variation. Methods: This qualitative study involved semi-structured interviews with 15 life-support trainers. Transcripts of the audio recordings were analyzed using a phenomenographic approach. Results: The analysis yielded 3 descriptive categories: (1) perception of PSLC, (2) use of PSLC in practice, and (3) reasons for deviation from PSLC. PSLC was generally considered valuable but also challenging. Common reasons to deviate from the standard strategy are related to trainer and learner factors and time constraints. Conclusions: The PSLC is perceived as a flexible yet complex debriefing framework, with considerable variation in how it is understood and applied. Key principles of the PSLC, as originally described, are not always utilized, which may negatively impact learning outcomes. To enhance consistency in applying these principles and to improve effectiveness, further faculty development to improve understanding of PSLC is recommended.